Sharing Data for Production Scheduling Using the ISA-95 Standard - Harjunkoski, Iiro; Bauer, Reinhard (Frontiers in Energy Research, 2014)
In the development and deployment of production scheduling solutions one major challenge is to establish efficient information sharing with industrial production management systems. Information comprising production orders to be scheduled, processing plant structure, product recipes, available equipment and other resources are necessary for producing a realistic short-term production plan. Currently, a widely-accepted standard for information sharing is missing. This often leads to the implementation of costly custom-tailored interfaces, or in the worst case the scheduling solution will be abandoned. Additionally, it becomes difficult to easily compare different methods on various problem instances, which complicates the re-use of existing scheduling solutions. In order to overcome these hurdles, a platform-independent and holistic approach is needed. Nevertheless, it is difficult for any new solution to gain wide acceptance within industry as new standards are often refused by companies already using a different established interface. From an acceptance point of view, the ISA-95 standard could act as a neutral data-exchange platform. In this paper, we assess if this already widespread standard is simple, yet powerful enough to act as the desired holistic data-exchange for scheduling solutions.